From genetics to biotechnology: Synthetic biology as a flexible course‐embedded research experience. Issue 6 (2nd September 2022) - Johnson, Kristen C.; Sabel, Jaime L.; Cole, Judith; Pruett, Christin L.; Plymale, Ruth; Reyna, Nathan S.
Abstract: The need for changing how science is taught and the expansion of undergraduate research experiences is essential to foster critical thinking in the Natural Sciences. Most faculty research programs only involve a small number of upper‐level undergraduate students each semester. The course‐based undergraduate research experience (CURE) model enables more students to take ownership over an independent project and experience authentic research. Further, by creating projects that fit into a curriculum's learning goals and student‐oriented outcomes, departments help strengthen critical thinking skills in the classroom. Here, we report on the incorporation of a synthetic biology CURE into a mid‐level cellular biology course and two advanced level genetics/molecular biology courses. Synthetic biology involves systematic engineering of novel organisms, such as bacteria and plants, to work as functional devices to solve problems in medicine, agriculture, and manufacturing. The value of synthetic biology and its ultimate utility as a teaching tool relies on reusable, standard genetic parts that can be interchanged using common genetic engineering principles. This Synthetic biology CURE effectively achieves five essential goals: (1) a sense of project ownership; (2) self‐efficacy: mastery of a manageable number of techniques; (3) increased tolerance for obstacles through challenging research; (4) increased communication skills; and (5) a sense of belonging in a larger scientific community. Based upon our student assessment data, we demonstrate that this course‐based synthetic biology laboratory engages students directly in an authentic research experience and models important elements of collaboration, discovery, iteration, and critical thinking.